A Review: Caring Practices of Songbird, Red-Whiskered Bulbul (Pycnonotus jocosus) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2016)
Pycnonotus jocosus is known as red-whiskered bulbul or known by local Malaysian as songbird or burung candik. Burung candik is one of the favourite pet birds’. Generally, it comes from Bangladesh, southern China, India, Nepal, north Peninsular Malaysia, Thailand and Vietnam (Animal Pest Alert: Red-whiskered Bulbul). Burung candik is favoured because of their ability in singing in east-coast region of Malaysia specifically. In this research, the caring practices are observed. All the result were recorded and documented through interview and experiment research. The caring practices concerned are housing and cage, bathing and grooming, singing feature and diet and feeding. The results showed that one cage equipped with one bird for comfort and to avoid fighting. The birds were needed to be bathed once in a week at least according to the bird’s willingness. General singing functions are to attract the mate and territorial defense. Feed given were insects, fruits and pellet.
Keywords: Caring practices; Red-whiskered bulbul; song-bird